The influence of the mass on the finish time in skeleton and luge competitions, and the fairness of rules and regulations - Fuss, F. K. (Sports Engineering, 2023)
In gravity-powered sports, more mass at the same drag area results in a shorter finish time. Based on the body mass data and the finish times of the Skeleton and Luge competitions at the 2018 Winter Olympics, this study investigated the fairness of rules, by establishing trends between finish time and body mass or simulated system mass. A glide model served for the assessment of the sensitivity of mass, drag area and coefficient of friction, and for determining how much mass were required to tie with the next higher rank of the first four athletes of each competition. The rules of Skeleton and Luge competitions permit the use of ballast mass as a function of the athletes` body mass, but the reference mass was up to 10 kg too low. When correlating the finish time with the body mass, all trends were significant (p = 0.032; a = 0.05) which indicated that the finish times were mass dependent. Correlating the finish time with the simulated system mass reveals the same result except for the men`s Luge competition. The sensitivity analysis showed that 15% change of an input parameter resulted in about 1% change of the finish time. Despite the low sensitivity, the masses required to tie with the next highest rank ranged from 0.02 to 20 kg, with a median of 0.7 kg. The skeleton rules were improved in 2020 which now provide equal conditions across a wide range of body masses; however, the current Luge rules still disadvantage lighter athletes even when using the permitted ballast mass.